The Fall and Rise of the Public in Public Education: From Hannah Arendt to Jürgen Habermas - Carusi, F. (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2026)
What makes a public and what meaning do theories of the public hold for public education? This paper takes up the work of two philosophers, Hannah Arendt and Jürgen Habermas, to argue that how the public is theorized is consequential for situating public education. The article begins with a brief overview of the U.S. federal education policy in terms of its neoliberalization of public education. I then consider Arendt’s theory of the public as a response to this policy discourse to argue that Arendt’s public results in the rise of the social at the expense of the public. I then highlight Habermas’s theory that maintains an opening for the public structured by its critical role. I conclude by emphasizing the importance of philosophy of education for continuing to conceptualize the public of public education.